ASSOCIATION BETWEEN BODY MASS INDEX AND CARDIORESPIRATORY FITNESS AMONG PATIENTS UNDERGOING CARDIAC STRESS TEST IN DR HASAN SADIKIN GENERAL HOSPITAL BANDUNG - Grace Octania; Mohammad Rizki Akbar; Sofiati Dian (PAIFORI, 2021)
Body mass index (BMI) and cardiorespiratory fitness are considered risk factors for cardiovascular disease. Chronic inflammation associated with adiposity as well as the hemodynamic changes that occur when there is an increase in BMI suggests a possible association between BMI and cardiorespiratory fitness. This study aims to analyze the relationship between BMI and cardiorespiratory fitness. A cross-sectional study was conducted using weighted cardiac training test results for the period January 1st, 2014 to December 31, 2019, from the Non-Invasive Diagnostic Division, the Department of Cardiology and Vascular Medicine, Dr. Hasan Sadikin Bandung. Subjects included in the study were those who achieved the maximum estimated heart rate based on age or less than 10 beats per minute, and/or the exercise test was stopped due to fatigue with a Borg 17 scale. Patients with multiple conditions were excluded from the study (taking beta-blockers, having a history of heart failure and diabetes mellitus, currently undergoing cardiac rehabilitation), along with patients with incomplete data. The maximum oxygen consumption in the form of the metabolic equivalent of tasks (METs) was estimated based on the speed and inclination of the stage reached during the treadmill training test using the Bruce protocol. The percentage of fitness is obtained by comparing the METs achieved with the estimated maximum METs based on age and gender. The relationship between BMI and percentage of fitness was analyzed using the Pearson correlation test. The total number of subjects included in the study was 51 subjects. The mean BMI of the subjects was 25.65 ± 3.22 kg / m2. The mean fitness percentage was 107.29 ± 23.89. Analysis of the relationship between BMI and fitness showed a negative but insignificant relationship (r = -0.135, p = 0.345). An increase in body mass index has a tendency to be associated with a decrease in cardiorespiratory fitness.